Characteristics of Lithofacies in Deep Shale Gas Reservoirs in the Southeast Sichuan Basin and Their Influence on Pore Structure - He, Jiang; Zhu, Songyue; Shi, Xuewen; Zhao, Shengxian; Cao, Lieyan; Pan, Shulin; Wu, Feng; Wang, Meng (Frontiers in Earth Science, 2022)
The characteristics of lithofacies in the shale reservoir of the Wufeng and Longmaxi formations located in the Luzhou gas field were studied using the three-end-member method (mineralogical components). In addition, the microscopic characteristics and pore genesis of different lithofacies were studied and compared using TOC, FESEM, and digital core images. The results of the present study showed the development of five lithofacies: (a) quartz rich argillaceous shale; (b) quartz / clay mixed shale; (c) calcareous/ clay mixed shale; (d) calcium rich argillaceous shale; and (e) clay rich siliceous shale. The degree of pore development between lithofacies was highly heterogeneous. In addition, data indicated that total shale porosity increased with the increase in TOC. Thus, pores were mainly related to organic matter. The enrichment of framboidal pyrite in quartz rich shale (S1, S-3) and mixed shale facies (M-2, M-3) is essential during the formation of high-quality reservoirs. On the other hand, the content of organic matter in clayey shale was low, which does not favor the development of high-quality reservoirs. Differences in lithofacies pore structures are controlled by the sedimentary environment. The strong retention and reduction environment are the most favorable features for the formation of organic rich siliceous shale lithofacies, which promote the preservation of organic matter and the development of reservoirs.